(untitled) (Bangladesh Pharmaceutical Journal, 2018)
The present study was aimed to isolate and investigate actinomycetes having antimicrobial and cytotoxic activities from soil samples of Mirzapur, Rajshahi, Bangladesh. Total 27 bacteria were isolated and initial screening found that Streptomyces species have low to moderate antagonistic property against various pathogenic bacteria and among them EFAI-1was quite interesting. The antimicrobial activity of crude ethyl acetate extract obtained from EFAI-1was determined using broth-dilution method against Bacillus cereus, Listeria monocytogenes, Staphylococcus aureus, Escherichia coli, Shigella sonnei and Salmonella typhi. The crude extract was almost equally active against both Gram-positive and Gramnegative bacteria. The highest zone of inhibition was found 21 mm at a concentration of 100 μg/disc against Salmonella typhi. The minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC) of the crude extract against the test bacteria were in the range of 15.6-125 μg/ml and 62.5-250μg/ml, respectively. We found that the LC50 value of the crude extract was only 0.13 μg/ml against brine-shrimp nauplii indicating its potent cytotoxic nature. Our results indicate that this bacterium would be an excellent source of potent antibiotic and anticancer drugs. Bangladesh Pharmaceutical Journal 20(2): 188-193, 2017